ONLINE CONSUMER REVIEW, BRAND COMMUNITY, TRUST AND CONSUMER PURCHASE DECISIONS IN INDONESIA - Vicky F Sanjaya; Shafira Jingga Hernita (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
This study examines the effect of online consumer reviews, brand community, and trust on purchasing decisions. The method used in this study was a cross-sectional survey design. The sample in this study were online consumers in Indonesia, with a total of 100 respondents. The statistical test was performed using the PLS-based Structural Equation Modeling. The validity test uses the loading factor value, while the reliability test uses the Cronbach's alpha value, composite reliability, and Average Variance Extracted (AVE). After all, the results of the indicator items used in this study were valid and reliable; then, the hypothesis was tested. Of the five hypotheses proposed, all are supported, but the fifth hypothesis is not significant. The conclusion of this study is the importance of maintaining the right quality products and services to get good consumer reviews. Besides that, it is also essential to maintain the brand community to continue to believe and make purchase decisions.